Avatar, the last airbender. [Part 1-3], North and south - Yang, Gene Luen (Avatar, the last Airbender., 2022)
Malina, a Northerner, is behind the change and plans to unify the Water Tribes, but Gilak, a Southerner, leads a fierce rebellion to stop her. In the face of these two opposing tribes, Katara will have to make peace with her nostalgia and mistrust to save the home she loves from being permanently torn apart.